How are trial outcomes prioritised by stakeholders from different regions? Analysis of an international Delphi survey to develop a core outcome set in gastric cancer surgery. - Bilal Alkhaffaf; Aleksandra Metryka; Jane M Blazeby; Anne-Marie Glenny; Paula R Williamson; Iain A Bruce; GASTROS International Working Group (PLoS ONE)
Background International stakeholder participation is important in the development of core outcome sets (COS). Stakeholders from varying regions may value health outcomes differently. Here, we explore how region, health income and participant characteristics influence prioritisation of outcomes during development of a COS for gastric cancer surgery trials (the GASTROS study). Methods 952 participants from 55 countries participating in a Delphi survey during COS development were eligible for inclusion. Recruits were grouped according to region (East or West), country income classification (high and low-to-middle income) and other characteristics (e.g. patients; age, sex, time since surgery, mode of treatment, surgical approach and healthcare professionals; clinical experience). Groups were compared with respect to how they categorised 56 outcomes identified as potentially important to include in the final COS ('consensus in', 'consensus out', 'no consensus'). Outcomes categorised as 'consensus in' or 'consensus out' by all 3 stakeholder groups would be automatically included in or excluded from the COS respectively. Results In total, 13 outcomes were categorised 'consensus in' (disease-free survival, disease-specific survival, surgery-related death, recurrence of cancer, completeness of tumour removal, overall quality of life, nutritional effects, all-cause complications, intraoperative complications, anaesthetic complications, anastomotic complications, multiple organ failure, and bleeding), 13 'consensus out' and 31 'no consensus'. There was little variation in prioritisation of outcomes by stakeholders from Eastern or Western countries and high or low-to-middle income countries. There was little variation in outcome prioritisation within either health professional or patient groups. Conclusion Our study suggests that there is little variation in opinion within stakeholder groups when participant region and other characteristics are considered. This finding may help COS developers when designing their Delphi surveys and recruitment strategies. Further work across other clinical fields is needed before broad recommendations can be made.